Análise das manifestações patológicas em pontes da rodovia RN-233 - Nobre, Gerson Talles Nogueira (Universidade Federal Rural do Semi-Árido, 2019)
Bridges are extremely important structures for society, they interconnect regions, enabling the transportation of goods and locomotion of people, directly affecting the economy and social relations of these places. Bridges can take varied forms and consist of many different materials, always seeking to satisfy conditions of stability, durability, functionality and local availability. In spite of their great importance, the bridges suffer constantly with executive failures and mainly the lack of maintenance, which can lead to the appearance of pathological manifestations, or even the absence of some element in them. This work aims to perform routine inspection and evaluation of existing pathologies, following the standard of inspection of bridges, viaducts and concrete walkways, NBR 9452: 2016 on the RN-233 highway Apodi à Caraúbas - RN. The inspection was carried out through photographic records obtained by visiting the seven analyzed bridges, and filling the frames provided for in standard, so that the bridges could have their structure, durability and functionality conditions classified as good, fair or poor, following the same standard . The results indicate that the main pathological manifestations are: corrosion of reinforcement, displacement of concrete, moisture spots and pavement wear and expansion joints, which imply a poor classification as regards structure. Regarding the constructive failures, these are related to the lack of most bridge protection devices, which results in a quersito also bad functionality. It is concluded that the analyzed bridges need corrective maintenance besides modifying the geometry in some cases.
Monografia
Keywords: OAE’s; Patologia; Inspeção; Rotineira; NBR 9452/2016; ENGENHARIAS::ENGENHARIA CIVIL